Joint adoption of sustainable practices in cocoa production systems - Pérez Marulanda, Lisset; Castro-Nuñez, Augusto Carlos (2022)
The objective of this document is to identify the determinants of the joint adoption of sustainable practices in the cocoa production systems To achieve the stated objective, this document uses information from 922 household surveys conducted in both departments and presents different types of analysis such as descriptive statistics multivariate and generalized ordered probit models.